Implikasi Zona Nilai Tanah Terhadap Pendapatan Asli Daerah di Kecamatan Tirawuta - Septian Jackrianto; L.M Golok Jaya; Fitra Saleh; Ahmad Hidayat; Al Firman (JAGAT (Jurnal Geografi Aplikasi dan Teknologi), 2024)
The Land Value Zone (ZNT) is interpreted as an area that represents the same land value on plots of land in certain region, the boundaries of which are in accordance with its landuse. ZNT is determined based on the market value of land, making it useful for determining land service rates, determining land transaction rates in the community, and as a basis for determining the Taxable Sale Value (NJOP) for Land and Building Taxes (PBB). This research was conducted in the Tirawuta District and aimed to: (1) Determine the Land Value Zone; (2) Determine the potential for regional original revenue (PAD) based on the Land Value Zone Map. In this study, a Land Value Zone map was created using a sales comparison approach that overlaid with the Tirawuta District Administrative Map and the 2022 PBB Block Map, then compared with the land value based on NJOP. The results of this study are: (1) There are 98 Land Value Zones with the highest land value of Rp.303.000/m2 in the Rate-Rate Subdistrict. While the lowest land value is Rp.6.000/m2 in Roko-Roko Subdistrict with an average standard deviation of 4,5%; (2) The increase in regional income based on the comparison between transaction prices and NJOP value is 457%.